Family History, Reproductive, and Lifestyle Risk Factors for Fibroadenoma and Breast Cancer. Issue 3 (10th December 2018) - Li, Jingmei; Humphreys, Keith; Ho, Peh Joo; Eriksson, Mikael; Darai-Ramqvist, Eva; Lindström, Linda Sofie; Hall, Per; Czene, Kamila
Abstract: Background: To understand which breast cancer (BC) risk factors also increase the risk of fibroadenoma and investigate whether these factors have the same effect in BC patients with previous fibroadenoma. Methods: Using multistate survival analysis on a large dataset (n = 58 322), we examined the effects of BC risk factors on transitions between three states: event-free, biopsy-confirmed fibroadenoma, and BC. Hazard ratios and corresponding 95% confidence intervals associated with covariate effects were estimated. Median follow-up time was 25.3 years. Results: The mean ages at diagnosis of fibroadenoma and BC were 42.6 and 48.3 years, respectively. Participant characteristics known to increase the risk of BC were found to increase the risk of fibroadenoma (family history of BC and higher education). Participant characteristics known to confer protective effects for BC (older age at menarche, more children, and larger childhood body size) were found to reduce fibroadenoma risk. The effect sizes associated with the direct transitions from event-free to fibroadenoma and BC were generally not different for the covariates tested. Age at fibroadenoma diagnosis was associated with the transition from fibroadenoma to BC (hazard ratioper year increase = 1.07 [95% confidence interval = 1.03 to 1.12]). Conclusion: We showed that biopsy-confirmed fibroadenomas shared many risk factors with BC. More work is needed to understand the relationships between fibroadenoma and BC to identify women who are at high risk of developing BC after a fibroadenoma diagnosis.